Vitamin D and cancer - Johnson, Candace S.; Trump, Donald L. [ (Donald Lynn)] , 1945- (Springer, 2011)
Substantial data indicate the broad importance of vitamin D-based signaling in normal human physiology and the broad effects of vitamin D deficiency. Vitamin D may play a role not only in the control of bone and mineral metabolism, but also appears to be involved in immune function, cardiovascular health, thrombosis and vasculogenesis and neuromuscular function. Considerable epidemiologic data demonstrate that low vitamin D serum levels occur very commonly in normal adult populations and that vitamin D deficiency is associated with an enhanced risk of cancer death from lung, prostate, head & n